Epithelial Wnt10a Is Essential for Tooth Root Furcation Morphogenesis. (March 2020) - Yu, M.; Liu, Y.; Wang, Y.; Wong, S.W.; Wu, J.; Liu, H.; Feng, H.; Han, D.
WNT10A (Wingless-type MMTV integration site family, member 10A) plays a crucial role in tooth development, and patients with biallelic WNT10A mutation and mice lacking Wnt10a show taurodontism. However, whether epithelial or mesenchymal WNT10A controls the initiation of the root furcation formation remains unclear, and the functional significance of WNT10A in regulating root morphogenesis has not been clarified. Here, we investigated how Wnt10a affects tooth root development by generating different tissue-specific Wnt10a conditional knockout mice. Wnt10a knockout in the whole tissue ( EIIa-Cre;Wnt10a flox/flox ) and in dental epithelium ( K14-Cre;Wnt10a flox/flox ) led to an absence of or apically located root furcation in molars of mice, a phenotype that resembled taurodontism. An RNAscope analysis showed that the dynamic epithelial and mesenchymal Wnt10a expression pattern occurred during root development. Immunofluorescent staining of E-cadherin and EdU revealed decreased epithelial cell proliferation at the cervical region of the molar in K14-Cre;Wnt10a flox/flox mice at postnatal day 0 (PN0), just before the initiation of root morphogenesis. Interestingly, we found increased pulpal mesenchymal cell proliferation in the presumptive root furcating region of the molar in K14-Cre;Wnt10a flox/flox mice at PN4 and PN7. RNA-seq indicated that among the Wnt ligands with high endogenous expression levels in molars, Wnt4 was increased after epithelial knockout of Wnt10a . The RNAscope assay confirmed that the expression of Wnt4 and Axin2 in the dental papilla of the presumptive root furcating region, where dental pulp overgrowth occurred, was increased in K14-Cre;Wnt10a flox/flox molars. Furthermore, after suppression of the elevated Wnt4 level in K14-Cre;Wnt10a flox/flox molars by Wnt4 shRNA adenovirus and kidney capsule grafts, the root furcation defect was partially rescued. Taken together, our study provides the first in vivo evidence that epithelial Wnt10a guides root furcation formation and plays a crucial role in controlling the organized proliferation of adjacent mesenchymal cells by regulating proper Wnt4 expression during root furcation morphogenesis.